Glochidion monostylum - Tsen, S.; Damit, A.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Glochidion monostylum is a shrub or tree endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 52 km2 and 9,545.3 km2, respectively. Although the AOO is calculated from known existing records, it is considered that the actual AOO may be considerably larger than this due to under sampling. It is represented in at least four protected areas and no major threat to the population of this species. Hence, it is assessed as Least Concern. Glochidion monostylum is endemic to Sabah, Malaysia.